2020
DOI: 10.1002/naaq.10161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Xanthophyll Supplementation on Growth Performance, Body Color, Carotenoids, and Blood Chemistry Indices of Chinese Soft‐Shelled Turtle Pelodiscus sinensis

Abstract: A 12-week experiment was conducted to investigate the effects of diets containing 0 (CD), 40 (X1), 80 (X2), and 120 mg/kg (X3) xanthophyll on the growth, body color, and blood chemistry of the Chinese soft-shelled turtle Pelodiscus sinensis. Four hundred and eighty turtles with initial weight of 37.90 AE 0.26 g were randomly stocked equally in 12 cement ponds (4.0 × 5.0 × 0.8 m) to form four groups in triplicate. The turtles were fed one of the four diets (crude protein 48%, crude lipid 6%) twice daily, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Studies also showed that adding lutein (70.3-239 mg/ kg) can promote SGR of Chinese soft-shelled turtles (4.81 ± 0.04 g) (Liu et al, 2013), and the optimal β-carotene level for turtle growth (mean weight: 5.7 g) was 49.1 mg/kg (Chen & Huang, 2011). Our previous research suggested that 80-120 mg/kg xanthophyll and 8% spirulina in the diet have an effective influence on the growth performance of turtles (He et al, 2019;Wang et al, 2020). However, studies in some kinds of fishes indicated that supplementation with carotenoids in feed had no effect on the growth (Shi et al, 2010;Yeşilayer et al, 2020, Abd El-Gawad et al, 2019.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies also showed that adding lutein (70.3-239 mg/ kg) can promote SGR of Chinese soft-shelled turtles (4.81 ± 0.04 g) (Liu et al, 2013), and the optimal β-carotene level for turtle growth (mean weight: 5.7 g) was 49.1 mg/kg (Chen & Huang, 2011). Our previous research suggested that 80-120 mg/kg xanthophyll and 8% spirulina in the diet have an effective influence on the growth performance of turtles (He et al, 2019;Wang et al, 2020). However, studies in some kinds of fishes indicated that supplementation with carotenoids in feed had no effect on the growth (Shi et al, 2010;Yeşilayer et al, 2020, Abd El-Gawad et al, 2019.…”
Section: Discussionmentioning
confidence: 95%
“…While the canthaxanthin ratio or canthaxanthin supplementation in feed and carotenoid content in the liver and plastron had no significant linear relationship. In a previous study, it was shown that there was a linear relationship between carotenoid contents in the liver and carapace skin and xanthophyll supplementation in feed (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This implies that the differential expression of Spats1 in different ages may be closely associated with the expression of testosterone. In addition, spermatogenesis of P. sinensis is initiated in the summer (June), and the mature spermatozoa are subsequently released from the epididymis in the autumn (October) [ 6 , 43 ]. In P. sinensis , the seminiferous epithelium is spermatogenically active in summer and autumn, but quiescent during the remaining part of the year [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. sinensis is an important species of aquaculture which is broadly spread in Asia. Since the fast growth of turtle farming, the economic value of P. sinensis has also increased [ 6 ]. Phylogenetic analysis revealed that P. sinensis is a relatively ancient tetrapod, and the study of the morphological evolution and reproductive patterns of the species is of great scientific value [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%